Bridging the Motivation Gap: Teachers' Application of AI Gemini in Fostering College Students' Autonomous Reading Habits - Edy Suseno; Dian Novita; Fika Megawati (English Department - University of Sultan Ageng Tirtayasa, 2026)
This study explores the integration of the Gemini AI model as a